A Faith-Innovation-Service Model for Christian Educational Entrepreneurship in Indonesia - Nella Mariana Panjaitan; Kristiani Yanti Kana; Delf G. Kalalo (Indonesian Journal of Christian Education and Theology, 2026)
This study examines the integration of entrepreneurship in Christian education as a response to globalization, digital transformation, and changing socio-economic demands. While previous studies have often treated entrepreneurship as a secular approach and Christian education as a theological enterprise, this study seeks to bridge this gap through an integrative framework relevant to the Indonesian context. Using a qualitative approach through a critical integrative literature review, this study analyzes scholarly literature through thematic analysis to identify patterns of entrepreneurial practices in Christian education and synthesize a conceptual framework. The findings reveal five major entrepreneurial practices in Christian education: faith-based curriculum innovation, visionary leadership, diversified funding strategies, community empowerment, and digital technology integration. This study contributes to the discourse on faith-based edupreneurship by offering an integrative model that connects theological values, educational innovation, and social mission.